Brown Tumors Belong to the Spectrum of KRAS-driven Neoplasms. (30th November 2022) - Turek, Daniel; Haefliger, Simon; Ameline, Baptiste; Alborelli, Ilaria; Calgua, Byron; Hartmann, Wolfgang; Harder, Dorothee; Flanagan, Adrienne M.; Amary, Fernanda; Baumhoer, Daniel
Abstract : Brown tumors are rare and generally self-limiting mass lesions of bone occurring in the context of hyperparathyroidism. Although commonly regarded as endocrine-driven tumor-like lesions, we detected pathogenic hotspot KRAS mutations in 10/16 brown tumors (62%) with similar frequencies found in cases affecting the peripheral and axial skeleton. Pathogenic mutations in other driver genes of the RAS-MAPK pathway were not identified. Our findings suggest brown tumors to represent true neoplasms driven by the activation of the RAS-MAPK signaling pathway. The frequent regression of brown tumors after normalization of hyperparathyroidism points to a second hit mediated by endocrine stimulation to be required for tumor development. Our findings underline the pathogenic relation of brown tumors to nonossifying fibroma and giant cell granuloma of the jaws which both appear histologically similar to brown tumors and are also driven by RAS-MAPK signaling pathway activation.